1998
DOI: 10.2527/1998.7671738x
|View full text |Cite
|
Sign up to set email alerts
|

Body composition at farrowing and nutrition during lactation affect the performance of primiparous sows: II. Milk composition, milk yield, and pig growth.

Abstract: Sows that were either fat or lean at farrowing (340 or 280 g of body fat/kg BW, respectively) were offered either a low-protein (LP; 7.9% CP and 15.5 MJ DE/kg as fed) or a high-protein (HP; 19.0% CP and 15.6 MJ DE/kg as fed) diet on an ad libitum basis throughout a 4-wk lactation to test the hypothesis that the amount of milk and its composition are responsive to the supply of endogenous (body reserves) and exogenous (diet) substrates. Pigs were weighed at birth and weekly during lactation, milk yield was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
46
2
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 15 publications
11
46
2
2
Order By: Relevance
“…The present experiment indicates that a higher feed intake during pregnancy increases the amount of body reserves at farrowing but results in lower voluntary feed intake and higher mobilisation of body reserves during lactation in agreement with previous data [7,9,36,[40][41][42]. In these previous studies, backfat thickness in fat sows at farrowing was in a similar range to ours (26.0 mm vs. 29.2 mm in [7], 28.1 mm in [9], 24.3 mm in [35,36], 29.4 mm in [41], about 30.0 mm in [42]).…”
Section: Discussionsupporting
confidence: 81%
“…The present experiment indicates that a higher feed intake during pregnancy increases the amount of body reserves at farrowing but results in lower voluntary feed intake and higher mobilisation of body reserves during lactation in agreement with previous data [7,9,36,[40][41][42]. In these previous studies, backfat thickness in fat sows at farrowing was in a similar range to ours (26.0 mm vs. 29.2 mm in [7], 28.1 mm in [9], 24.3 mm in [35,36], 29.4 mm in [41], about 30.0 mm in [42]).…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were reported by ESTIENNE et al (2000). REVELL et al (1998b) showed that during four weeks of lactation, the litters of lean sows grew 16 % faster than the piglets fed by sows with higher fat reserves (1.92 vs. 1.66 kg/day). In this study, litter birth weight was significantly higher in group I than in group II due to the difference in litter size.…”
Section: Discussionsupporting
confidence: 78%
“…Litter size increased from the first until the fifth parity. In an experiment performed by REVELL et al (1998b), smaller litters and more stillbirths were reported in obese sows than in lean ones. YOUNG et al (2004) did not observe any differences in the total number of births, live births, stillbirths, mummified fetuses and weaned piglets between fat and lean sows, but they noted that sows with a very high fat content were more likely to produce smaller litters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the lactation period, the major changes were observed in the ash fraction which increased by 35%. Several studies have been reported on sows' milk composition (Klobasa et al, 1987;Revell et al, 1998;Alston-Mills et al, 2000), most of which focused on evaluating the protein, fat and lactose milk content. However, there is little information on the mineral composition of the sow milk, and none related to IB sows' milk.…”
Section: Milk Compositionmentioning
confidence: 99%